2012
DOI: 10.5539/gjhs.v5n2p84
|View full text |Cite
|
Sign up to set email alerts
|

Myths and Fallacies about Male Contraceptive Methods: A Qualitative Study amongst Married Youth in Slums of Karachi, Pakistan

Abstract: Pakistan presently has one of the largest cohorts of young people in its history, with around 36 million people between the ages of 15 and 24 years. One of the main reasons for high population growth in Pakistan is almost stagnant contraceptive prevalence rate of 30% nationally and 17.4% amongst youth. The study was conducted to explore the perceptions regarding myths and fallacies related to male contraceptive methods among married youth aged 18-24 year in Karachi, Pakistan. Qualitative exploratory study desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 24 publications
1
31
1
4
Order By: Relevance
“…Sonraki benzer çalışmanın ise 26 yıl sonra literatüre kazandırılmıştır. Kontraseptif yöntemlere ilişkin mitlerin çiftlerin cinsel doyumunu olumsuz etkilediği düşünüldüğünde, 13,[16][17][18][19] bu alandaki çalışma yılları aralığının fazla olması, sayısının sınırlı olması bu sistematik derlemenin dikkat çeken bulgularındandır.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Sonraki benzer çalışmanın ise 26 yıl sonra literatüre kazandırılmıştır. Kontraseptif yöntemlere ilişkin mitlerin çiftlerin cinsel doyumunu olumsuz etkilediği düşünüldüğünde, 13,[16][17][18][19] bu alandaki çalışma yılları aralığının fazla olması, sayısının sınırlı olması bu sistematik derlemenin dikkat çeken bulgularındandır.…”
Section: Discussionunclassified
“…8 Literatürde, erkeklerin kullandığı kontraseptif yöntemlere ilişkin mitlerin cinsel sağlık üzerine olumsuz etkiye sahip olduğu ortaya koyulmuştur. 13,[16][17][18] Mitler, özellikle kondom kullanımında sınırlılıklara neden olmaktadır. 18 Yapılan çalışmalarda erkeklerin kondom kullanımına ilişkin en yaygın kaygılarının, cinsel memnuniyetin azalması, 17,19 ereksiyon bozukluğu, enfeksiyon, 13,16,18 bel ağrısı, baş ağrısı, eklem ağrısı 18 ve baş dönmesi 13,16 olduğu saptanmıştır.…”
unclassified
See 1 more Smart Citation
“…The research studies done in Pakistan and Delhi also reported worries that vasectomy would cause impotency and weakness (Singh et al, 2003;Nishtar et al, 2012). In Shih et al's the women and men from all racial/ethnic groups reported a fear of longterm effects of vasectomy on sexual function.…”
Section: )mentioning
confidence: 99%
“…In our study, using condoms would cause a decrease in sexual performance and pain was identified as the primary concern. In a qualitative study done in Pakistan with married couples between the ages of 18 to 24, the participants thought that using condoms would cause sexual reluctance, particularly low back pain and infection (Nishtar, Sami, Faruqi, Khowaja, & Ul-Hasnain, 2012).…”
Section: )mentioning
confidence: 99%